The imaginary and the everyday as motivating elements for the conformation of the urban space - García C, Luz Marcela (UNIVERSIDAD DE SONORA, 2023)
The imaginary as an intangible element present in society manifests itself as a fundamental component in the formation of the individual and the conformation of the collective. The operational forms developed by him, within a city such as everyday life, can be altered by the social imaginary contained in its context, to the point of breaking their daily narratives. This relationship is fundamental, since it is part of the development of the individual in his current future, and his participation in the constructed scenarios and his future projection. Under these theoretical foundations, a deductive conceptual analysis is developed in this article through a bibliographic review of imaginaries and everyday life, with the aim of establishing theoretical positions to support design projects aimed at recognizing these themes, for the resolution of problems and evolution of urban contexts. From this bibliographic review, a case study will highlight the influence of the urban context and the imaginaries, in their daily development and future aspirations of individuals, as well as the possible actions in their urban context, all through observations and methodological analysis made from the storytelling tool.